Delayed Dominant-Negative TNF Gene Therapy Halts Progressive Loss of Nigral Dopaminergic Neurons in a Rat Model of Parkinson's Disease - Harms, Ashley S (Nature Publishing Group, 2011)
Parkinson's disease (PD) is a progressive neurodegenerative disorder typified by the loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc). Recent evidence indicates that neuroinflammation may play a critical role in the pathogenesis of PD, particularly tumor necrosis factor (TNF). We have previously shown that soluble TNF (solTNF) is required to mediate robust degeneration induced by 6-hydroxydopamine (6-OHDA) or lipopolysaccharide. What remains unknown is whether TNF inhibition can attenuate the delayed and progressive phase of neurodegeneration. To test this, rats were injected in the SNpc with lentivirus encoding dominant-negative TNF (lenti-DN-TNF) 2 weeks after receiving a 6-OHDA lesion. Remarkably, when examined 5 weeks after the initial 6-OHDA lesion, no further loss of nigral DA neurons was observed. Lenti-DN-TNF also attenuated microglial activation. Together, these data suggest that TNF is likely a critical mediator of nigral DA neuron death during the delayed and progressive phase of neurodegeneration, and that microglia may be the principal cell type involved. These promising findings provide compelling reasons to perform DN-TNF gene transfer studies in nonhuman primates with the long-term goal of using it in the clinic to prevent the delayed and progressive degeneration of DA neurons that gives rise to motor symptoms in PD.